Does Maternal Employment Affect Breastfeeding in Plateau State, Nigeria? - Emmanuel, Andy; Clow, Sheila Elizabeth (Africa Journal of Nursing and Midwifery, 2018)
There are competing priorities between maternal employment and breastfeeding. This study was conducted to determine the influence of the maternal employment status and the time of return to work postpartum on breastfeeding. This will provide vital information that could be used in promoting breastfeeding among working mothers in the future. A cross-sectional study of 763 pregnant women who had previously given birth was conducted in Plateau State, Nigeria. Data were collected using a validated questionnaire and the women participated voluntarily. Exclusive breastfeeding for at least five months was recorded in 75.4 per cent (270/358) of employed women and 78.4 per cent (225/287) of unemployed women. An overall duration of 13 months’ breastfeeding was reported in 72.9 per cent (256/351) of women who were working at the time of the birth compared to 84 per cent (241/287) of women who were not working. For the overall duration of breastfeeding (any breastfeeding), results revealed that women who return to work early after delivery are more likely to stop breastfeeding earlier than the recommended period. Maternal employment at the time of delivery may therefore have an influence on breastfeeding. Accordingly, working mothers in this setting require additional breastfeeding support or counselling, and also, workplace breastfeeding support in Plateau State requires evaluation.